THE METHODS OF PRODUCTION OF EXPANDED THIN-SHELLED POROUS MODELS IN CASTING BY INVESTMENT PATTERNS - I. G. Sapchenko; S. G. Zhilin; O. M. Komarov (Литьë и металлургия, 2005)
It is shown that porous extracting models produced under the developed technology have high size and geometrical accuracy during the whole time slot of storage and correspond to the 9-10^ class of accuracy, what is higher than the traditional investment patterns have.